(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
The international higher education sector has been witnessing an economic and soft power competition by the nation-states and has become a part of global power competition. It is worth inquiring about the role of international education in future diplomacy after the Covid-19 pandemic outbreak as there are likely to be substantial changes in the forms of deliveries, operations and policies in the international higher education activities and global politics. This brief essay highlights the possible effects of Covid-19 pandemic on the relationship of international higher education with diplomacy and international relations. It provides food for thoughts for the researches in the area.